Superficial CD34-positive fibroblastic tumor in the forearm of a middle-aged patient: A newly described, rare soft-tissue tumor - Bharat Rekhi; Devmalya Banerjee; Kunal Gala; Ashish Gulia (Wolters Kluwer Medknow Publications, 2018)
Superficial CD34-positive fibroblastic tumor is a recently described soft-tissue tumor entity. A 48 year-old-male presented with a gradually increasing soft-tissue mass in his right forearm of 2 years' duration, along with multiple subcutaneous soft-tissue nodular lesions, and reminiscent of lipomas over his body. He underwent a wide excision of his forearm mass. Microscopic sections showed a circumscribed tumor in the dermis and subcutaneous fat, composed of spindle cells, inflammatory cells, including lymphocytes, plasma cells, and eosinophils, along with interspersed markedly pleomorphic giant cells containing moderate-to-abundant "glassy" cytoplasm, vesicular nuclei, exhibiting prominent nucleoli, and intranuclear pseudoinclusions. There were no significant mitotic figures, areas of hemorrhage, necrosis, or pigment histiocytes. By immunohistochemistry, the tumor cells were diffusely positive for CD34 while negative for cytokeratin (CK), pan CK (AE1/AE3), S100 protein, CD30, and CD31. MIB1/Ki-67 was low and highlighted 4%-5% tumor nuclei. Diagnosis of superficial CD34-positive fibroblastic tumor was offered. Sections from the various resection margins were free of tumor. Postresection, the patient is alive with no evidence of disease for the past 8 months. This constitutes as one of the first case reports of this rare tumor entity from our country. Its diagnostic and treatment implications are discussed herewith.